DINAMIKA PENYUSUNAN ANGGARAN DAERAH : KASUS PROSES PENETAPAN PROGRAM DAN ALOKASI ANGGARAN BELANJA DAERAH DI KABUPATEN SLEMAN - Hanida, Rozidateno Putri (Pusat Penelitian Politik, 2010)
The article is a study of the dynamics of local budget arrangement especially in the process ofprogram decision and local budget expenses allocation in Sleman region Other dynamics in this study is the establishment ofegosectoral of division ofplanning namely SKPD in Sleman region In this regards planning proposal arrangedby SKPD has not showedpriority scale but rather compilation ofproposal that are reservedfrom process ofplanning It can be said that the SKPD proposal is premature therefore SKPD attempts to reserve budget expenseswithout considering budget limitation andprogram continuation in other SKPD The dynamics inpoliticalprocess islegislative body in Sleman region that is oriented to constituent interests hence neglecting the benefit ofaprogramand the value oftrickle down effect of a program On both levels there have been dynamics that show interactionbetween actors by sharing and bargaining interests The implication ofthis dynamics is that budgetingpolicy cannot increase society welfare instantly and an effective and efficient budget is difficult to achieve